Patients’ Experiences of Ending Massage Therapy Care: A Commentary - Baskwill, PhD, MSc, BEd, RMT, Amanda; Michaud, BA, RMT2, Suzanne (International Journal of Therapeutic Massage & Bodywork, 2020)
Patients are best positioned to provide information about their experiences of healthcare services; however, their perspectives are often underutilized. During informal discussions with massage therapists (MTs), and through the authors’ own professional experiences, it was noted that there are times when patients decide independently, and without notice, to end the care they are receiving. To date, no research has been published exploring the experiences of patients who choose to discontinue massage therapy care and there is a gap in the quality assurance process of MTs. Lack of understanding of patients’ experiences is a missed opportunity to strengthen the therapeutic relationship, ensure patient safety, improve treatment quality, and develop professionally. To affect change within multiple levels of the profession so that patients’ experiences are valued and solicited in a manner that allows patients to provide critical feedback, we recommend two initial actions. First, we challenge massage therapy stakeholders to consider alternate research methodologies and methods to explore this phenomenon. Second, we recommend that MTs cultivate an appreciation for constructive criticism and actively listen to their patients with confidence.